Development of intra canopy vertical boom sprayer for maize (Zea mays) crop under hill farming conditions - AYUSH; SATPATHY, SANGRAM KISHOR (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2022–2024 at College of Agricultural Engineering and Post-Harvest Technology Central Agricultural University, Imphal, Manipur), Ranipool, Sikkim to determine discharge rate, swath width, spray angle and CV at different pressure and height combinations of three commercially available nozzles. The flat fan nozzle was selected with lowest CV of 30.26% at operating pressure of 150 kPa and 400 mm nozzle height. The selected nozzle was used in a vertical boom and tested under simulated conditions in the laboratory at different pressures and forward speeds to access the intra canopy spraying on test maize (Zea mays L.) plants at different positions (Adaxial and Abaxial) and the optimum speed and pressure was found to be 0.42 m/s and 150 kPa. Then a small, lightweight manually guided power sprayer for intra canopy spraying in maize crop was developed and evaluated in the field conditions. The experiment was laid out in a completely randomized design (CRD) with 16 treatments (4×4) and total of 48 experiments with three replications of each treatment. Good above leaf and under leaf deposition with 70.81 and 58.66 deposits/cm2 respectively were observed in field trials. The volume deposition above leaf and under leaf were found to be 70.35 and 58.14 µL/cm2, respectively. The sprayer had a field capacity of 0.11 ha/h with field efficiency of 73.33%. The cost of developed sprayer was ₹22,600. The benefit cost ratio and payback period of developed sprayer was estimated to be 1.56 and 1.7 years, respectively. The sprayer can be adopted by small farmers in the NEH region under terrace farming conditions.